Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/ldr.4089
|View full text |Cite
|
Sign up to set email alerts
|

Ephemeral gully erosion in concentrated flow channels induced by rainfall and upslope inflow on steep loessial slopes

Abstract: Ephemeral gullies (EGs) play a crucial role in hydrological connectivity, soil erosion, and land degradation. However, little research has focused on flow hydraulics in concentrated flow channels and their effects on EG erosion on steep loessial slopes. A simulated experiment of rainfall (60-120 mm hr À1 ) and upslope inflow (0.45-2.25 m 2 hr À1 ) were conducted on concentrated flow channels with loess at 15 -25 slope gradients. The concentrated flow was turbulent and subcritical in most cases.The flow shear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Therefore, more attention should be paid to bank erosion of gullies on AF in the Lhasa River basin than in other regions. Kang, Guo, & Wang (2021) concluded that toe scour freed the hanging soil material on the sidewall, which accelerated gully bank collapse. Chaplot (2013) proposed that lateral seepage may be the main factor for bank expansion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, more attention should be paid to bank erosion of gullies on AF in the Lhasa River basin than in other regions. Kang, Guo, & Wang (2021) concluded that toe scour freed the hanging soil material on the sidewall, which accelerated gully bank collapse. Chaplot (2013) proposed that lateral seepage may be the main factor for bank expansion.…”
Section: Discussionmentioning
confidence: 99%
“…All these researches verified the off‐site effect of the hydrological connectivity in catchment on gully erosion. Meanwhile, several works evidence that gullies also provide access to runoff, improve hydrological connectivity, and accelerate runoff generation in catchment (Bracken & Croke, 2007; Kang, Guo, & Wang, 2021; Molina et al, 2009; Monsieurs et al, 2015). For example, Croke et al (2005) found that the maximum distance of runoff transport in the gullies was 2–3‐times longer than that in the dispersive pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Runoff scouring experiments have been widely employed to study slope erosion processes (Kang et al, 2021; Sun et al, 2022). During the experiments, water is released into a slope to reproduce the initiation and development of erosion processes (Bai et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Gully length development has been systematically studied in terms of its correlation with average daily rainfall, flow discharge, and catchment area [15][16][17]. Gully depth and width increase with flow discharge [18]. A dynamic model of gully erosion, established by Sidorchuk et al, is used to predict the development of gully depth and width, and involves longitudinal profile, flow velocity, water shear stress, and coefficient of flow resistance [6].…”
Section: Introductionmentioning
confidence: 99%